Influence of oxygen uptake kinetics on physical performance in youth soccer - Doncaster, G.; Marwood, S.; Iga, J.; Unnithan, V. (European Journal of Applied Physiology, 2016)
Purpose: To examine the relationship between oxygen uptake kinetics (VO2 kinetics) and physical measures associated with soccer match play, within a group of highly trained youth soccer players. Methods: Seventeen highly trained youth soccer players (age: 13.3 ± 0.4 year, self-assessed Tanner stage: 3 ± 1) volunteered for the study. Players initially completed an incremental treadmill protocol to exhaustion, to establish gaseous exchange threshold (GET) and VO2max (59.1 ± 5.4 mL/kg/min). On subsequent visits, players completed a step transition protocol from rest-moderate-intensity exercise, followed by an immediate transition, and from moderate- to severe-intensity exercise (moderate: 95 % GET, severe: 60 %Delta), during which VO2 kinetics were determined. Physical soccer-based performance was assessed using a maximal Yo-Yo intermittent recovery test level 1 (Yo-Yo IR1) and via GPS-derived measures of physical soccer performance during soccer match play, three 2 × 20 min, 11 v 11 matches, to gain measures of physical performance during soccer match play. Results: Partial correlations revealed significant inverse relationships between the unloaded-to-moderate transition time constant (tau) and: Yo-Yo IR1 performance (r = -0.58, P = 0.02) and GPS variables [total distance (TD): r = -0.64, P = 0.007, high-speed running (HSR): r = -0.64, P = 0.008 and high-speed running efforts (HSReff): r = -0.66, P = 0.005]. Conclusion: Measures of VO2 kinetics are related to physical measures associated with soccer match play and could potentially be used to distinguish between those of superior physical performance, within a group of highly trained youth soccer players.